1991
DOI: 10.1111/j.1751-1097.1991.tb02090.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Variations in Ultraviolet Sunlight Reaching the Biosphere: . Calculations for the Past Three Decades

Abstract: The long-term data base on atmospheric ozone combined with a set of radiative transfer calcu!ations provides estimates of the variability in ultraviolet (UV) sunlight that should ha\ e occurred over the period 1957-1988 under clear, pollution-free skies. Results refer to the earth's surface at specific locations in the Northern Hemisphere and to averages over collections of sites located in three latitude bands from 30 to 64"N. For any one year the annually integrated solar irradiance, weighted by the action s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…7 While there have been numerous studies 8 -10 exploring the supposed increase in surface UV radiation resulting from stratospheric ozone decline, 11 none have consistently observed any increasing longterm trend. 12 Experimental observations have indicated that random variability in the attenuating properties of the troposphere will obscure the effect of stratospheric ozone trends. 13 Surface values of UV radiation can be derived from satellite measurements 14 -17 and provide global coverage and the nearly continuous monitoring needed for longterm trend analysis.…”
Section: Introductionmentioning
confidence: 99%
“…7 While there have been numerous studies 8 -10 exploring the supposed increase in surface UV radiation resulting from stratospheric ozone decline, 11 none have consistently observed any increasing longterm trend. 12 Experimental observations have indicated that random variability in the attenuating properties of the troposphere will obscure the effect of stratospheric ozone trends. 13 Surface values of UV radiation can be derived from satellite measurements 14 -17 and provide global coverage and the nearly continuous monitoring needed for longterm trend analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased levels of ozone in the stratosphere from organochlorine contamination are resulting in higher levels of UV-B radiation reaching the surface of the earth (Frederick, 1990;Frederick et al, 1991;Kerr and McElroy, 1993). Within the UV-B spectral region, the relative enhancement in irradiance resulting from ozone depletion is disproportionately greater at shorter wavelengths (Caldwell et al, 1989).…”
mentioning
confidence: 99%
“…In contrast, model studies and measurements [Justus, 1992] show that the TUVR response to ozone change is very small (less than 0.2% per 1% change in ozone). Therefore the downward trend of RB irradiance in Figure 1 (by about 10%) is too large (and the upward TUVR trend in Figure 2 is much too large) to be attributed to expected global or regional changes in total ozone column over the study period [Madronich, 1992;Frederick et al, 1991]. It should be noted here that the word "trend" is used synonymously with "year-to-year variations over the 4-year study period."…”
Section: Figure 2 Presents the Rb/global Ratios Ofmentioning
confidence: 99%